2008
DOI: 10.1016/j.bone.2008.07.248
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride effects on bone formation and mineralization are influenced by genetics

Abstract: Introduction-A variation in bone response to fluoride (F − ) exposure has been attributed to genetic factors. Increasing fluoride doses (0ppm, 25ppm, 50ppm, 100ppm) for three inbred mouse strains with different susceptibilities to developing dental enamel fluorosis (A/J, a "susceptible" strain; SWR/J, an "intermediate" strain; 129P3/J, a "resistant" strain) had different effects on their cortical and trabecular bone mechanical properties. In this paper, the structural and material properties of the bone were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 38 publications
3
68
0
7
Order By: Relevance
“…Previous studies demonstrated that fluoride leads to the proliferation of osteoblasts, promotes their differentiation and modulates (20). Fluoride also increases alkaline phosphatase-specific activity and promotes bone formation in rats in vivo (21). However, excess fluoride may give rise to a number of adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that fluoride leads to the proliferation of osteoblasts, promotes their differentiation and modulates (20). Fluoride also increases alkaline phosphatase-specific activity and promotes bone formation in rats in vivo (21). However, excess fluoride may give rise to a number of adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…In B6 calvaria cells, there were signals more striking of fluoride effect than in the C3 osteoblasts [19], and the B6 calvaria cells were more responsive to inhibitory action of NaF. Some evaluations, in general between C3 and B6, have shown C3 mouse with more stability or resistance to factors/agents that can modify the bone metabolism [22,24,35,36].…”
Section: Discussionmentioning
confidence: 94%
“…Fluoride exposure showed no significant effect on bone microarchitecture in three mice strains [24]. Osteoid nodules formed in cultures of fetal rat calvarial cells exposed to fluoride inhibited the initiation phase during mineralization at low Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Os ossos imersos em NaF (0,145, 0,5 ou 2 M) apresentaram menor resistência e dureza, e uma maior deformação comparado ao osso não tratado, tanto na tensão (DEPAULA et al 2002;KOTHA et al 1998) quanto na compressão (WALSH;. Com altas doses de F (2,0 M NaF), um aumento significativo foi também observado na dureza (DEPAULA et al 2002) (CHACHRA et al 1999;MEYER 1978;HAILER 1998;MOUSNY et al 2008;TURNER et al 1997). …”
Section: Lista De Abreviaturas E Siglasunclassified
“…Para cada extrato foram realizados géis SDS, catiônico e aniônico, além do mapa proteômico. Esta linhagem foi escolhida por apresentar uma característica peculiar de resistência aos efeitos do F nos tecidos mineralizados (CARVALHO et al 2009;EVERETT et al 2002;MOUSNY et al 2006;MOUSNY et al 2008) ARAKAWA et al 1994;NEURATH;ERICKSON;COOPER 1942). O agente desnaturante funciona também como uma barreira para agregação durante o renovelamento da proteína, devido ao efeito caotrópico do desnaturante e as interações entre o desnaturante e a proteína.…”
Section: Caracterização Das Proteínas De Fêmur De Camundongo Da Linhaunclassified